Batas Usia Perkawinan Dalam Undang-Undang Nomor 16 Tahun 2019: Analisis Psikologi Dan Maslahah Mursalah - Aziz, Abdul (STAINI Press, 2022)
This study aims to explain how the marriage age limit is in accordance with Law Number 16 of 2019 according to the Maslahah Mursalah theory. Marriage Law Number 1 of 1974 stipulates that marriage is only permitted if the prospective groom is 19 years old and the bride is 16 years old. With the passage of time, these provisions have become outdated and are not in accordance with the current situation both in terms of psychology, biological health, education, and economy. The age limit for marriage has undergone two Judicial Review submissions to the Constitutional Court regarding the age limit for marriage. Islam does not regulate the age limit for a person to get married. By increasing the marriage age for women to 19 years, in order to provide protection for children who are still underage so that they are more prepared biologically and psychologically. Therefore, it is suggested that this regulation can be used as a reference and applied to prevent underage marriages.